The Influence of Promotion on Repurchase Interest Mediated by Cash-On-Delivery Payments on Tiktok Shop - Nazarina, Tiara; Santi, Ira Nuriya; Ponirin, Ponirin; Wirastuti, Wiri (Celebes Scholar pg, 2025)
In the shifting landscape of digital commerce, where attention is monetized and trust remains precarious, promotions alone no longer suffice to sustain consumer behavior. This study interrogates the relationship between promotional stimuli and repurchase interest within TikTok Shop, situating Cash-on-Delivery as a mediating variable that reconfigures how consumers interpret value, risk, and reliability. Drawing on quantitative data from urban Indonesian consumers and tested through a structural equation model, the findings reveal that promotional effectiveness is contingent not only on its visibility or appeal but on the presence of structural reassurance that transforms interest into intention and intention into behavior. Cash-on-Delivery, often relegated to logistical convenience, emerges here as a psychological architecture that stabilizes trust in a landscape shaped by speed and spectacle. Rather than acting as an isolated payment method, it becomes the mechanism through which promotional rhetoric is translated into credible action. In a digital environment where persuasion is abundant but safety is scarce, platforms that fail to integrate these dimensions do not merely lose transactions. They lose relevance. This study argues that the future of social commerce lies not in amplifying promotional volume but in curating transactional conditions where trust is embedded, not assumed. The implication is clear. Behavioral continuity in digital markets will belong not to the loudest voice but to the most structurally coherent experience.